PENDEKATAN TIPOLOGI DALAM PENGEMBANGAN PARTISIPASI MASYARAKAT - N. Saribanon (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Residential solid waste is being a critical problem in many cities including Jakarta. Community-based management is the most important strategy even when sophisticated treatment such as bio-energy or waste industrial park would be implemented soon, as every waste processing needs separated wastes. Increasing the participation through community-based management is more effective than change people’s perception and behavior on domestic wastes. In some cases, to change community behavior in waste separation and recycling need more than ten years i.e. at Kampong Banjarsari, but with appropriate support system on social planning only took two years i.e. Kampong Rawajati. The implementation constraint of this programme is on replication or expandability of the programme to implemented in another place. There are also lack of government’s significant efforts to push and to support that action. It’s true that some communities develop the same model, but without acceleration and expandable programme, the significance of that effort is very poor. This study tried to ellaborate the model of a system based on spatial analyses to determine residential typology and found five residential types i.e. high,middle-high,middle,middle-lower and lower level of residential, quantitative analyses to determine typology of community participation and found four types of community participation i.e. moral-normative, moral-remunerative, calculative-remuneraive and calculative- coercive. Qualitative analyses had been ellaborated to determine authority or goverment policies typology especially on strengthening the government institution and limiting the scope of government function. Breaking down from these classification, three strategies could develop, namely community participation strategy, infastructure development strategy and institutional management strategy.Implementation of these models could accomodate the heterogeneity ofcommunities and give positive impact on social acceptability.